Owners' Characteristics and the Financial Bootstrapping Strategies Used by Rural Small Businesses in South Africa - Maurice Nchabeleng; Olawale Fatoki; Olabanji Oni (Journal of Economics and Behavioral Studies, 2018)
The purpose of this study was to examine if there are significant differences in the financial bootstrapping strategies of rural small businesses on the basis of owners' demographic characteristics (level of education and gender). The research followed a quantitative research method with descriptive research design. A sample of 104 rural small businesses participated in the survey. Data was collected through the use of self-administered questionnaires in a survey. The participants in the study were rural small business owners in Fetakgomo Municipality located in the Limpopo Province of South Africa. The study utilised the convenience and snowball sampling techniques to select the study participants. Data analysis included descriptive statistics, factor analysis and the T-test. The Cronbach alpha was used to measure reliability. The results of the T-test showed significant differences between gender and level of education and the financial bootstrapping methods used by rural small businesses. Recommendations are made to improve the awareness of bootstrapping by small business owners.